Meilensteine der Grammatikentwicklung im dritten Lebensjahr: Eine Untersuchung anhand elizitierter Sprachproduktion mit einem neu entwickelten Analyseverfahren. - Kauschke, Christina; Schmidt, Hanna; Tenhagen, Anne (Forschung Sprache)
During the third year of life, children go through important developmental stages in the area of grammar. In German, for example, the acquisition of verb placement is a central milestone of this developmental phase. Previous findings on grammar acquisition have been obtained by parent questionnaires or by time-consuming analyses of children's spontaneous speech. Based on an elicited production task, the present study aimed at describing typical trajectories of grammatical development in the third year of life (milestones), and at identifying potential warning signs. For this purpose, utterances of 98 monolingual German children between 2;0 and 2;11 years of age were elicited using colored pictures of everyday situations. The utterances were then transcribed and analyzed. In addition to determining the length (MLU) and complete ness of the utterances, a new method is introduced, designed along the lines of the IPSyn (Altenberg et al., 2018). Language samples are searched for instances of specific morphological and syntactic phenomena, and calculated using a computerized procedure. The results suggest that key milestones of grammatical development in the third year of life can be assessed and specified. The newly developed, economic instrument proves to be suitable for research and diagnostic purposes.